All-optical NRZ wavelength conversion based on a single hybrid III-V/Si SOA and optical filtering - Wu, Yingchen; Huang, Qiangsheng; Keyvaninia, Shahram; Katumba, Andrew; Zhang, Jing; Xie, Weiqiang; Morthier, Geert; He, Jian-Jun; Roelkens, Gunther (Optics Express, 2016)
The rapid growth of the internet and internet-related services call for large-capacity and highspeed data networking. All-optical networking allows for data reconfiguration directly in the optical layer rather than in the electronic layer. Since no optical-to-electrical-to-optical (OEO) data conversions are involved, power consumption and bandwidth of such communication networks can be substantially improved. An important function that needs to be implemented for all-optical networks is all-optical wavelength conversion (AOWC). For example, in wavelength division multiplexed (WDM) networks AOWC can remove wavelength blocking in optical cross connects [1]. AOWC based on semiconductor optical amplifiers (SOA) has a number of advantages, including high-speed operation and easy integration with other optoelectronic and passive waveguide components. Many SOA-based AOWC techniques on the InP platform have been reported, achieving data rates up to 320 Gb/s [2–6], based on cross-gain modulation (XGM), cross-phase modulation (XPM) or four wave mixing (FWM). 2R/3R regeneration and the wavelength conversion of advanced modulation format signals have also been realized using SOA-based Mach-Zehnder interferometric structures [7, 8]. Most experiments are carried out using a Return-to-Zero (RZ) data format, while the Non-Return-to-Zero (NRZ) data format is still the dominant one in commercial optical networks. AOWC for NRZ signals has been reported by means of an SOA-MZI based push-pull structure [9], bidirectional driving schemes [10] or a differentially-biased scheme
Keywords: Optical NRZ wavelength conversion; Hybrid III-V/Si SOA; Optical filtering